The impacts of land reforms on water infrastructure use and investment: A case study of the Biri dam, Zimbabwe. (October 2021) - Simango, Bilton; Mabiza, Collin; Gumindoga, Webster; Mhizha, Alexander
Abstract: This paper sought to answer the question, how did Zimbabwe land reforms impact on water use, property rights and investment in water infrastructure? This was done for Biri dam in Middle Manyame subcatchment. Landuse and landcover changes from 1984 through the land reform period to 2019 were analysed through GIS and remote sensing techniques. Water allocation and dam levels records were analysed to understand water use patterns within the subcatchment in the aftermath of the land reforms. Interviews were used to investigate perceptions on property rights and investment in water infrastructure. The study found that construction of the Biri dam coincided with the commencement of the Fast-Track Land Reform Programme. As a part of the reform process, the custodianship of the Biri dam was moved to the national water authority. Consequently, farmers who had invested in the dam lost their investment. Changes in land ownership affected water use, so much that between 2007 and 2020 the dam mostly maintained water storage levels above 70%. The study attributed the 85% decrease in land put under irrigation from 1984 to 2019 to the land reforms. Municipal water use, rather than agriculture for which the dam was primarily constructed, has now become the largest water user in the subcatchment. The study concluded that land reforms impacted negatively on water utilization and loss of investment in water infrastructure. The study recommends that land and water changes be implemented concurrently, taking into account how changes in one resource affects the other. Highlights: Zimbabwe's Fast-Track Land Reform Programme affected water utilization. White commercial farmers lost their investment in water infrastructure. Satellite image classification shows significant decrease in irrigation land from 1984 to 2019. Policy disharmony among farmers, the subcatchement council, the national water authority. Land and water reforms must take place simultaneously to yield benefits in water sector.